1997
DOI: 10.1037/0893-164x.11.4.261
|View full text |Cite
|
Sign up to set email alerts
|

Overview of 1-year follow-up outcomes in the Drug Abuse Treatment Outcome Study (DATOS).

Abstract: The Drug Abuse Treatment Outcome Study (DATOS) collected 1-year follow-up outcomes for 2,966 clients in outpatient methadone (OMT), long-term residential (LTR), outpatient drug-free (ODF), and short-term inpatient (STI) programs in 1991-1993. LTR, STI, and ODF clients reported 50% less weekly or daily cocaine use in the follow-up year than in the preadmission year. Reductions were greater (p < .01) for clients treated for 3 months or more. Clients still in OMT reported less weekly or daily heroin use than clie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
381
3
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 562 publications
(420 citation statements)
references
References 29 publications
29
381
3
7
Order By: Relevance
“…This class of medications is highly regulated in the US, with clinics and prescribing physicians facing specific regulatory requirements (Jaffe and O'Keefe, 2003). A large literature has established methadone maintenance (MMT) as an evidence-based treatment for opiate dependence (Hubbard et al, 1997;Mattick et al, 2003;Ward et al, 1999;NIH, 1997). MMT has tended to be concentrated within a treatment sector consisting of opioid treatment programs (OTPs) that exclusively dispense this medication.…”
Section: Introductionmentioning
confidence: 99%
“…This class of medications is highly regulated in the US, with clinics and prescribing physicians facing specific regulatory requirements (Jaffe and O'Keefe, 2003). A large literature has established methadone maintenance (MMT) as an evidence-based treatment for opiate dependence (Hubbard et al, 1997;Mattick et al, 2003;Ward et al, 1999;NIH, 1997). MMT has tended to be concentrated within a treatment sector consisting of opioid treatment programs (OTPs) that exclusively dispense this medication.…”
Section: Introductionmentioning
confidence: 99%
“…NTORS, in addition to other key drug treatment outcome studies, Drug Abuse Treatment Outcome Study (DATOS) (Hubbard et al, 1997), Australian Treatment Outcome Study (ATOS) (Teeson, et al, 2005), and the Drug Outcome Research Study in Scotland (DORIS) (McKeganey, et al, 2006), found signifi cant reductions in both drug use and criminal activity at follow-up. These fi ndings were more prominent for those that had been retained in treatment for three months or more (Hubbard, et al, 1997). The increased government spend on drug treatment in recent years and the widespread introduction of pro-active referral schemes, in particular the Drug Interventions Programme, has introduced greater heterogeneity amongst drug services' clients than that present a decade ago.…”
Section: Contextmentioning
confidence: 99%
“…Recognition of the harms associated with problem drug use, and the chronic nature of this condition, has lead to increased availability of treatment and/or rehabilitative services in Ireland under the National Drug Strategy (2001). Although international studies support the overall effectiveness of established treatment options available for problem drug users (Anglin, Hser, & Grella, 1997;Gossop, Marsden, Stewart, & Kidd, 2003;Hubbard, Craddock, Flynn, Anderson, & Etheridge, 1997;Teesson et al, 2006), to date, no national longitudinal data have been available to determine the effectiveness of such treatment options in the Irish context. Treatment evaluation research has traditionally relied upon outcome studies as a logical first step in understanding effectiveness.…”
Section: Introductionmentioning
confidence: 99%